PENERAPAN NUANSA BUDAYA MELAYU DI DEPARTMENT FOOD AND BEVERAGE SERVICE HOTEL IBIS PEKANBARU - Rindi Santika; Andi M Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
In accordance with the design, namely Riau Privincial government in 2020 which makes Riau as malay cultural centers, hotels in Riau Province has begun implementing a nuanced hotel malaycultural.This study used a descriptivemethod is by using the 9 key informan. With techniques to collect date through interviews to key informan are selected according to the research that is done by snawball sampling where the authors interviewed key informan to obtain the desired information.From the results of research conducted in the field with the study of malay cultural nuances in the department of food and beverage service ibis pekanbaru using the application of the theory of cultural, namely : as a giver of beauty and pleasure, as an entertainment provider, as a symbolic sacrifice, as a communication tool. From the results of this study at the ibis pekanbaru already started implementing malay cultural nuances.Key words : Implementation, malay cultural nuances, Ibis Riau